(untitled) (Journal of Economic Research & Business Administration, 2015)
In the article we’ve analyzed all accumulated experience of Kazakhstan in field of cluster initiatives. Basing on progressive foreign practice of cluster policy we justified all advantages related to innovative clusters building. Most of important methodological approaches to the creation and development of clusters also have been observed here. We suggested the ways of management influence for cluster’s forming with a view to procure the competitiveness of the national economy of the Republic of Kazakhstan. The ways include both directions: direct and indirect government support. The main ways are identified: direct financial support; tax exemptions; simplification of administrative procedures; infrastructure development, including innovation; information and marketing support.